PS02.204: GASTRIC TUBE CANCER AFTER ESOPHAGECTOMY FOR ESOPHAGEAL CANCER: A SYSTEMATIC REVIEW. (14th September 2018) - Gentile, Damiano; Riva, Pietro; Da Roit, Anna; Basato, Silvia; Marano, Salvatore; Castoro, Carlo
Abstract: Background: Gastric conduit used for reconstruction after esophagectomy for esophageal cancer (EC) has the potential to develop a metachronous cancer known as gastric tube cancer (GTC). The aim of our study was to review literature and evaluate outcomes and possible treatment strategies for GTC. Methods: A comprehensive systematic literature search was conducted using PubMed. No restriction was set for type of publication, number, age and sex of patients. Study language was limited to English. Characteristics of EC and its treatment and GTC and its treatment were analyzed. Results: A total of 26 studies were analyzed, 10 retrospective analysis and 16 case reports, involving 170 patients, 17 patients (10%) were affected by multifocal GTC. 143 ECs (84, 1%) were squamous cell carcinomas. In 95 patients (55, 9%) a posterior-mediastinal reconstructive route was used at the time of esophagectomy for EC. Mean interval between esophagectomy and diagnosis of GTC was 67, 18 months (4–236 months). 184 GTCs were metachronous lesions (98, 4%). 164 GTCs were adenocarcinomas (98, 2%). 84 GTCs were located in the lower part of the gastric tube. 88 patients were endoscopically treated. 63 patients underwent surgery. 30 total gastrectomies + limphoadenectomy with colon or jejunal interposition were performed. 27 subtotal gastrectomies and 6 wedge resections were performed. Main reported post-operative complications were: anastomotic leak, vocal cord palsy and respiratory failure. 19 patients were treated with chemoradiotherapy and palliative care. 68, 2% of endoscopically treated patients, 63, 5% of surgically resected patients and 5, 2% of patients who underwent chemoradiotherapy were alive at a mean follow-up of 25, 5 months. Feasibility of endoscopic resections in patients diagnosed with superficial GTC has been established. Surgical treatment represents the preferred treatment modality in operable patients with locally invasive tumor. Patients treated with conservative therapy have a scarce prognosis. Conclusion: Yearly endoscopic follow-up is of paramount importance in patients who underwent esophagectomy for EC with gastric tube reconstruction. At least, a 10-year endoscopic surveillance is recommended. Disclosure: All authors have declared no conflicts of interest.